Overcoming immunosuppression as a new immunotherapeutic approach against pancreatic cancer - Bazhin, Alexandr V.; Bayry, Jagadeesh; Umansky, Viktor; Werner, Jens; Karakhanova, Svetlana (OncoImmunology, 2013)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest types of malignancy. Via a broad stimulation of the immune system, PDAC activates both antitumor immune responses and immunosuppressive mechanisms. We propose that new immunotherapeutic strategies for the management of PDAC should be designed to specifically neutralize the immunosuppressive tumor microenvironment.
Gesehen am 16.11.2020